Satire in J.J. R. Jolobe's literary works : a critique in relation to contemporary South Africa - Benayo, Xolela (Rhodes University, Faculty of Humanities, School of Languages and Literatures, 2020)
J.J.R. Jolobe is regarded as one of the individuals who made a valuable contribution to the development of isiXhosa literature through his works, notably in his poetry (Ilitha, Umyezo; Jolobe 1936). His poetry ranges from abstract subjects to more philosophical matters. This study is aimed at decoding the manner in which he employs satire to conscientise African people of the then horrible situation that they were facing. With that said, poetry will not be the only work that this thesis analyses in the process of evaluating Jolobe's satire; his essays will also be examined (Amavo; Jolobe 1940). Based on the writings of various authors specialising in the subject, satire has been deemed to be a style of literary writing, one which involves invective satire. For the researcher, that statement will be rebutted, as it will be argued that the mode of satire need not be wholly invective. Jolobe's light-hearted satire not only showcases the amusing side of his writings, but also indicates the seriousness with which they were intended. Themes covered in Jolobe's satire have inspired the researcher to evaluate these literary texts in relation to modern contexts, especially when it comes to the relationship between the lines of the author's experience and the public. With that said, the social role of satire is something that one cannot deny. One could therefore say that there is an urgent need for African satirists to face the existing social and economic reality as authentically as possible. The voice of a satirist should also echo the voice of their society as a whole. Satirical study in post-colonial Africa, in South Africa in particular, is useful due to the idea that the works of the likes of Jolobe may diminish in significance due to neo-colonialism. In fact, this is the point which is considered in this study of Jolobe's satire. This study also examines stages afforded to the development of satire in Africa, especially in the post-colonial era. The purpose is to identify the effects of satire that are related to socio-political as well as religious factors. These factors are often seen as those that play a vital role is one's personal morals, and those that are meant to shape the whole community. Jolobe addresses imperialism and the class struggle, which speaks to the society's loyalties regarding the mobilization toward realizing the dream of being independent. This speaks to the works analysed, revealing protests against oppression and exploitation by imperialists; such works show how inhumane people could be against those who they deem to be beneath their standards. Researchers like Mahlasela (1973), Sirayi (1985), Kwetana (2000) and Khumalo (2015) are amongst those who have made it a point to study Jolobe to ensure that these works are kept alive, along with their significance. Other prospective researchers can follow suite in researching the great Jolobe. In ensuring that the aims of this study come to light, the researcher will be using socialist realism as a way of seeing that the works of Jolobe are realistic in nature. With that said, there will be an exploration of allegoric satire. Satiric allegory will be evaluated with regard to the view that it represents a unique slant on satire, whereby it deems satire to be more than just a supportive method of literary criticism. This allows the researcher to hold the view that satire should not be a restrictive framework when dealing with African literature. Satire as a modern form of criticism can be viewed as having an element of humanism, which would result in the satirist doing all he can to make sure that what is satirized is not isolated from the struggle of the community. It is for the above-mentioned reasons that we see a big challenge in the future development of satiric discourse in African literature.
Keywords: Jolobe, James J. R.; Xhosa literature -- History and criticism; Xhosa poetry -- History and criticism; Humor in literature; Xhosa literature -- Humor; Xhosa language